Small molecules targeting endocytic uptake and recycling pathways - Placidi, Giampaolo; Mattu, Clara; Ciardelli, Gianluca; Campa, Carlo C. (Frontiers in Cell and Developmental Biology, 2023)
Over the past years a growing number of studies highlighted the pivotal role of intracellular trafficking in cell physiology. Among the distinct transport itineraries connecting the endocytic system, both internalization (endocytosis) and recycling (endocytic recycling) pathways were found fundamental to ensure cellular sensing, cell-to-cell communication, cellular division, and collective cell migration in tissue specific-contexts. Consistently, the dysregulation of endocytic trafficking pathways is correlated with several human diseases including both cancers and neurodegeneration. Aimed at suppress specific intracellular trafficking routes involved in disease onset and progression, huge efforts have been made to identify small molecule inhibitors with suitable pharmacological properties for in vivo administration. Here, we review most used drugs and recently discovered small molecules able to block endocytosis and endocytic recycling pathways. We characterize such pharmacological inhibitors by emphasizing their target specificity, molecular affinity, and biological activity and impact in both in vitro and in vivo experimental models.